El Excentrico, 1955-09-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
September 20, 1955 [20 de septiembre de 1955]. Ano 5, No 22. Cover has an illustration of Don Miguel Hidalgo y Costilla, who is more well-known as the "Father of Mexican Independence" because of his role as the leader of the Mexican War of Independence. The illustration was displayed in celebration of the 145th anniversary of that war. The cover also displays a photo of Ana Maria Espinoza, who has achieved the title of queen of the court of honor established the Mexican Honor Commission, which was supervised by the Consulate General of Mexico.